Prinsip Murid Sebagai Pemimpin Menurut Matius 20:26-28 - Sunardi, Agus (Sekolah Tinggi Teologi Borneo, 2021)
Abstract: The character or nature of a servant presents a part of his daily activities or activities,namely as a person who serves. Or it can be said that service is a straightforward thing entrustedby an employer or master to him. The decision to determine everything is not in the hands of aservant but the decision is in the hands of his master. Without having a servant's heart is veryimpossible to do by a spiritual leader In involving this interesting discussion, it turned out that theApostles Paul, Peter, and Prophet Moses had also taken an important role in this warmdiscussion about leadership. Each of them has strong enough arguments to answer leadershipproblems according to the standards of inspired truths through the power of holy spirit.In discussing further theological theologies of Jesus Christ as a centralized figure inspiritual leadership as in this Journal about